2018
DOI: 10.21470/1678-9741-2018-0130
|View full text |Cite
|
Sign up to set email alerts
|

Which Method to Use for Surgical Ablation of Atrial Fibrillation Performed Concomitantly with Mitral Valve Surgery: Radiofrequency Ablation versus Cryoablation

Abstract: ObjectiveThe effects of energy source on the maintenance of sinus rhythm and the contribution of demographic characteristics to the case selection in patients submitted to ablation performed concurrently with mitral valve surgery were analyzed.MethodsCryothermal (n=42; 43.8%) and radiofrequency (n=54; 56.3%) energy were employed in 96 patients submitted to mitral valve replacement and Cox maze IV procedure. Patients were called for control visits between 15 days and 12 months after discharge. The causal relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 28 publications
(42 reference statements)
2
12
0
Order By: Relevance
“…Nevertheless, the 1 and 5-year freedom from AF at follow-up of this experience (98.1% and 89.2%, respectively) were comparable (or compared favorably) with those of other studies of Literature [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] where either biatrial (75% to 91% and 80.2%, respectively) or isolated LA ablation (57.8% to 95% and 72% to 81.1%, respectively) was performed. The present authors have no convincing arguments to give reason of these good results, which were consistent with the higher rate of dismission of any anti-arrhythmic drug of this experience with respect to other experiences (97.3% vs. 63% to 88.4%, at 1 year from hospital discharge) [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] . These results were even more unexpected considering that the line connecting the left pulmonary veins box to the LA appendage was waived and that an endocardial purse-string suture was used to perform the LA appendage obliteration (when performed).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Nevertheless, the 1 and 5-year freedom from AF at follow-up of this experience (98.1% and 89.2%, respectively) were comparable (or compared favorably) with those of other studies of Literature [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] where either biatrial (75% to 91% and 80.2%, respectively) or isolated LA ablation (57.8% to 95% and 72% to 81.1%, respectively) was performed. The present authors have no convincing arguments to give reason of these good results, which were consistent with the higher rate of dismission of any anti-arrhythmic drug of this experience with respect to other experiences (97.3% vs. 63% to 88.4%, at 1 year from hospital discharge) [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] . These results were even more unexpected considering that the line connecting the left pulmonary veins box to the LA appendage was waived and that an endocardial purse-string suture was used to perform the LA appendage obliteration (when performed).…”
Section: Discussionsupporting
confidence: 83%
“…Actually, in the literature, there is a relative lack of information concerning specifically the ablation of AF in isolated MV surgery (i.e., not combined with aortic valve operations), and it is know that the probability of success of surgery of AF in the case of concomitant correction both of mitral and aortic valvulopathy is higher than that of concomitant treatment of mitral valve disease alone [21] . Also the higher rate of patients of the study who died in-hospital (5.9% [5.3% ± 5.2% by EuroSCORE II] vs. 0–3% of Literature [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] ), and the fact that these high-risk subjects were (obviously) excluded from the calculation of the nonparametric estimates of freedom from AF at follow-up, may have improved the results significantly. Incidentally, the increased rate of in-hospital deaths of the present study was ascribed by the authors to the frequent (21.2%) presence of ischemic heart disease among the causes of MV disease, to the high rate of urgent surgical priority (25.4%), and to the prolonged time of surgery (an average of 5 h).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, TE events occurred only in three patients in the early postoperative period and no further TE events occurred in the six-month follow-up period. Vural et al [24] , in their recently published article (2018), have presented a comparison of cryoablation and radiofrequency ablation in MVS. They reported that there was no difference between the energy sources used for conversion to SR from AF.…”
Section: Discussionmentioning
confidence: 99%